HUBUNGAN SIKAP PESERTA BIMBINGAN PERKAWINAN PRA NIKAH TERHADAP NIAT MEMBINA KELUARGA SAKINAH - admin; Ahmad Majidun (Wahana Islamika: Jurnal Studi Keislaman, 2018)
Pre-marital guidance for married age teenagers is important to do, so the Ministry of Religion of Magelang Regency organizes the program in collaboration with Syubbanul Wathon Tegalrejo Boarding School. From the implementation of this activity, it is expected that participants who take part in this program have knowledge about how to build a confident family. This knowledge can ultimately shape the attitudes of participants towards sakinah family development and ultimately foster their intention to build a peaceful family. Thus the purpose of this study is to analyze whether attitudes have a positive relationship with the intention of fostering a healthy family. The research sample was 100 respondents with a research questionnaire as a data collection tool. The data analysis used is Structural Equation Modeling using SmarPLS software. The results of hypothesis testing prove that there is a positive and significant relationship between attitudes with the intention of participants to build a family with a relationship value of 0.529 or 52.9.